Islamic scriptures and voice intonation: a preliminary survey in Arabic linguistic thought and hadīth interpretive discourse - Jamil, Khairil Husaini (Penerbit Universiti Sains Malaysia, 2019)
This is the first study that aims to explore the possibility of applying the art and science of voice intonation in reading statements attributed to the Prophet Muhammad and to form a theoretical framework explicative of the nexuses between the two enterprises. The study ventures to assess the attention towards a range of functions played by voice intonation such as attitudinal functions, psychological functions and other indicative functions as it may have appeared within the various compositional strategies of ḥadīth literature. It also aims to examine how normal conversations, declarative sentences, questions, etc. could be identified through voice intonation and the extent to which the understanding of a certain ḥadīth can be affected by such an exercise. The preliminary analysis indicates that the right selection of tone assumes a crucial role in forming a sound ḥadīth interpretation. The consequential extension of this study may involve several other subtopics in the field such as the oral and written transmission of ḥadīth, the euphony and cacophony of narrated words and sentences in ḥadīth, and the psycho-spiritual effects of ḥadīth.